OPTIMALISASI STRATEGI PEMASARAN PADA UMKM: STUDI KASUS PIZZA PUTRA BUNGSU - Novia Azizah; Lintang Farrah K; Radithya Akmal Al Jalal; Raka Pratama K; Athifa Kirana W; Muhammad Nadif (Cahaya Ilmu Bangsa, 2025)
This study aims to formulate an effective marketing strategy for Pizza Putra Bungsu, a micro, small, and medium-sized enterprise (MSME) in the culinary sector, to enhance its operational sales. Using a qualitative approach, the study analyzes the internal and external conditions of the business through SWOT analysis, PESTEL analysis, and Porter’s Five Forces analysis. The findings indicate that Pizza Putra Bungsu's main strengths lie in product innovation and the quality of raw materials, while weaknesses include suboptimal marketing strategies. This research recommends strategic actions such as leveraging digital marketing, strengthening partnerships with local suppliers, and continuous product innovation to enhance competitiveness and sustainability in an increasingly competitive market.